Liberalism as a Way of Life - Lefebvre, Alexandre (Princeton University Press, 2024)
Why liberalism is all you need to lead a good, fun, worthy, and rewarding life-and how you can become a better and happier person by taking your liberal beliefs more seriouslyWhere do you get your values and sensibilities from? If you grew up in a Western democracy, the answer is probably liberalism. Conservatives are right about one thing: liberalism is the ideology of our times, as omnipresent as religion once was. Yet, as Alexandre Lefebvre argues in Liberalism as a Way of Life, many of us are liberal without fully realizing it-or grasping what it means. Misled into thinking that liberalism is confined to politics, we fail to recognize that it's the water we swim in, saturating every area of public and private life, shaping our psychological and spiritual outlooks, and influencing our moral and aesthetic values-our sense of what is right, wrong, good, bad, funny, worthwhile, and more. This eye-opening book shows how so many of us are liberal to the core, why liberalism provides the basis for a good life, and how we can make our lives better and happier by becoming more aware of, and more committed to, the beliefs we already hold.A lively, engaging, and uplifting guide to living well, the liberal way, Liberalism as a Way of Life is filled with examples from television, movies, stand-up comedy, and social media-from Parks and Recreation and The Good Place to the Borat movies and Hannah Gadsby. Along the way, you'll also learn about seventeen benefits of being a liberal-including generosity, humor, cheer, gratitude, tolerance, and peace of mind-and practical exercises to increase these rewards.You're probably already waist-deep in the waters of liberalism. Liberalism as a Way of Life invites you to dive in